1997
DOI: 10.1099/00221287-143-11-3599
|View full text |Cite
|
Sign up to set email alerts
|

A novel 27 kDa lipoprotein antigen from Mycobacterium bovis

Abstract: A novel Mycobacterium bovis antigen was identified from an expression library using sera from naturally infected cattle. The Escherichia coli recombinant clone expressed a 27 kDa protein, named P27. A rabbit serum against the recombinant antigen recognized a protein of 27 kDa in cellular extracts from M. bovis and M. tuberculosis. No protein was recognized in the culture supernatant. Sequence analysis indicated that P27 has a molecular mass of 24 kDa, showing a characteristic signal sequence for lipoprotein mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
41
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 36 publications
3
41
0
Order By: Relevance
“…LprG also has no described function in M. tuberculosis and no homology with other bacterial lipoproteins. LprG from M. bovis is recognized by serum from infected cattle suggesting that it is expressed during infection (39). Immunization with recombinant LprG was detrimental in a murine M. tuberculosis infection model consistent with the vaccine studies with LpqH (40).…”
Section: Discussionsupporting
confidence: 72%
“…LprG also has no described function in M. tuberculosis and no homology with other bacterial lipoproteins. LprG from M. bovis is recognized by serum from infected cattle suggesting that it is expressed during infection (39). Immunization with recombinant LprG was detrimental in a murine M. tuberculosis infection model consistent with the vaccine studies with LpqH (40).…”
Section: Discussionsupporting
confidence: 72%
“…The fact that the 30-kDa band was not radiolabeled indicates that the labeling is not due to nonspecific lipid absorption. Furthermore, it has been shown that the 27-kDa antigen has a signal peptidase type II site (7). For E. coli, the signal peptidase II enzyme required diacylglyceryl modification prior to cleavage (20,26); this means that diacylglyceryl mod- FIG.…”
Section: Discussionmentioning
confidence: 99%
“…Much less information exists about the protein product encoded by lprG. Immediately upstream of Rv1410c is lprG, which codes for LprG, a lipoprotein with no conserved enzymatic or functional domains save for the lipid attachment site that defines lipoproteins (1). LprG is a secreted, surface-expressed lipoprotein and has been shown to modulate host immune function (7).…”
mentioning
confidence: 99%